Efektivitas Penegakan Hukum terhadap Illegal Fishing di Laut Natuna Utara Pasca 2020 - Meltia Seca; Binsar Manurung; Rezky Abet Nego Simanjuntak; Ema Septaria (AHKAM, 2026)
Illegal fishing in the North Natuna Sea after 2020 remains a serious threat to Indonesia’s maritime sovereignty and the sustainability of national marine resources. This area has a strategic position, is rich in fishery resources, and directly borders several countries, making it vulnerable to illegal fishing activities by foreign vessels. This study aims to analyze the effectiveness of law enforcement against illegal fishing in the North Natuna Sea after 2020, identify the obstacles encountered, and formulate strategies for strengthening maritime law enforcement policies. This study used a normative juridical method with statutory and case approaches. Data were obtained through a literature review of relevant regulations, official reports, and scientific literature. The results showed that the Indonesian government has strengthened law enforcement efforts through integrated maritime patrols, interagency cooperation, the implementation of stricter sanctions, and the reinforcement of the roles of authorities such as the Indonesian Navy (TNI AL) and the Ministry of Marine Affairs and Fisheries. However, the effectiveness of law enforcement still faces obstacles in the form of limited facilities and infrastructure, the vastness of the surveillance area, and international political pressure. These findings confirm that a diplomatic approach remains necessary to maintain maritime sovereignty without triggering open conflict. Thus, law enforcement against illegal fishing in the North Natuna Sea requires a comprehensive and sustainable strategy through regulatory strengthening, capacity building for law enforcement officials, and the optimization of regional and international cooperation. This study contributes to the development of more effective maritime policies for addressing illegal fishing in Indonesian waters.